2014
DOI: 10.1111/are.12539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofLactobacillus plantarumas a water additive on host associated microflora, growth, feed efficiency and immune response of giant freshwater prawn,Macrobrachium rosenbergii(de Man, 1879)

Abstract: A 90‐day experiment was conducted by rearing 1020 prawn juveniles (0.54 ± 0.03 g) in water supplemented with three different concentrations of probiotic bacteria viz. T1 (107 cfu L−1), T2 (108 cfu L−1), T3 (109 cfu L−1) and the control (C) (unsupplemented water), to evaluate probiotic effect of Lactobacillus plantarum. In the present study, the growth parameters (WG%, SGR) and feed utilization parameters (FCR, PER) significantly improved (P < 0.05) in T3. The growth and feed utilization parameters though impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 79 publications
2
13
2
3
Order By: Relevance
“…A significant increase in immune indices caused by dietary B. pumilus was also reported in Nile tilapia (Oreochromis niloticus)(Srisapoome & Areechon, 2017) and striped catfish (Pangasianodon hypophthalmus)(Truong Thy et al, 2017).Hemocytes play a vital role in phagocytosis, nodule formation, encapsulation, hemocyte clumping, production of microbicidal compounds, mediation of cytotoxicity and so on(Johansson, Keyser, Sritunyalucksana, & Söderhäll, 2000;Smith, Brown, & Hauton, 2003), all of which have been proven to be an important part of the innate immunity of crustaceans. THC was not affected by dietary B. pumilus in the present study, which was not consistent with the results found inDash et al (2016), in which the THC of M. rosenbergii was increased by L. plantarum doses of 1 × 10 8 and 1 × 10 9 CFU/g diet.However, other indices associated with hemocytes, for example phagocytic activities, RBs activity and immune enzyme activity, were all enhanced by dietary B. pumilus. The modulation of phagocytic activity is considered a prompt and vital effect of dietary probiotics on the immune function of crustaceans (Irianto & Austin, 2002).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…A significant increase in immune indices caused by dietary B. pumilus was also reported in Nile tilapia (Oreochromis niloticus)(Srisapoome & Areechon, 2017) and striped catfish (Pangasianodon hypophthalmus)(Truong Thy et al, 2017).Hemocytes play a vital role in phagocytosis, nodule formation, encapsulation, hemocyte clumping, production of microbicidal compounds, mediation of cytotoxicity and so on(Johansson, Keyser, Sritunyalucksana, & Söderhäll, 2000;Smith, Brown, & Hauton, 2003), all of which have been proven to be an important part of the innate immunity of crustaceans. THC was not affected by dietary B. pumilus in the present study, which was not consistent with the results found inDash et al (2016), in which the THC of M. rosenbergii was increased by L. plantarum doses of 1 × 10 8 and 1 × 10 9 CFU/g diet.However, other indices associated with hemocytes, for example phagocytic activities, RBs activity and immune enzyme activity, were all enhanced by dietary B. pumilus. The modulation of phagocytic activity is considered a prompt and vital effect of dietary probiotics on the immune function of crustaceans (Irianto & Austin, 2002).…”
contrasting
confidence: 99%
“…However, the increased activity of amylase and protease in the dietary B. pumilus groups may have led to higher digestion and absorption of nutrients(Ziaei- Nejad et al, 2006), then the growth performance of M. rosenbergii may have been improved. Furthermore, studies in zebra fish, Danio rerio, demonstrated that some probiotics, for example Lactobacillus rhamnosus, could modulate the transcription of genes related to the differentiation and maturation of some tissues, thereby enhancing the growth of the animals(Avella et al, 2012;Gioacchini et al, 2011;Maradonna et al, 2013).The immune indices, including phagocytic activities and RBs activity, and the enzyme activity of PO, CAT, ACP and NOS were all significantly higher in all dietary B. pumilus groups than in the control group, and a higher survival rate was induced by dietary B. pumilus.Similar results have been observed in M. rosenbergii fed with other probiotics, such as Vibrio NE17(Rahiman, Jesmi, Thomas, & Hatha, 2010), Bacillus licheniformis(Kumar et al, 2013) and L. plantarum(Dash et al, 2016). A significant increase in immune indices caused by dietary B. pumilus was also reported in Nile tilapia (Oreochromis niloticus)(Srisapoome & Areechon, 2017) and striped catfish (Pangasianodon hypophthalmus)(Truong Thy et al, 2017).Hemocytes play a vital role in phagocytosis, nodule formation, encapsulation, hemocyte clumping, production of microbicidal compounds, mediation of cytotoxicity and so on(Johansson, Keyser, Sritunyalucksana, & Söderhäll, 2000;Smith, Brown, & Hauton, 2003), all of which have been proven to be an important part of the innate immunity of crustaceans.…”
supporting
confidence: 83%
“…Some authors have stated the effective concentration to obtain the best results in growth, survival, as well as in the prawn's immune response. In this sense, Dash et al (2016) evaluated the growth, food efficiency, biochemical composition, and response to three different concentrations (1×10 7 , 1×10 8 , 1×10 9 CFU L -1 ) of a probiotic (Lactobacillus plantarum). They found that they were significantly higher than in control (without probiotic).…”
Section: Probiotic Concentration and Dosementioning
confidence: 99%
“…in M. rosenbergii [47]. The probiotics play an important role in healthy maintenance gut micro lora of the host, which prevents colonization of harmful bacteria and stimulates the immune system [48][49][50][51].…”
Section: Gut Microbial Populationmentioning
confidence: 99%